Особливості управління європейськими академічними університетськими мережами - Ірина Чистякова (Pavlo Tychyna Uman State Pedagogical University, 2014)
Статтю присвячено розгляду особливостей управління європейськими академічними університетськими мережами. З'ясовано сутність понять «мережування навчальних закладів», «інноваційна освітня мережа», «університетська мережа», «академічна університетська мережа». Подано авторську класифікацію університетських мереж. Представлено змістові засади діяльності провідних академічних університетських мереж - Europaeum, The Coimbra Group, Utrecht Network. Виявлено спільні ознаки управляння досліджуваними мережами. Статья посвящена рассмотрению особенностей управления европейскими академическими университетскими сетями. Выяснено сущность понятий «сетевизация учебных заведений», «инновационная образовательная сеть», «университетская сеть», «академическая университетская сеть». Дана авторская классификация университетских сетей. Представлены содержательные основы деятельности академических университетских сетей - Europaeum, The Coimbra Group, Utrecht Network. Выявлены общие характеристики управления исследуемыми сетями. The article is devoted to the peculiarities of the management of the European University academic networks. The author notes that it is necessary to develop high quality education based on the promotion of cooperation at national and supranational levels. This task should carry out the educational networks, which form a new system of relationships between higher education institutions, which is determined by the stability and the efficiency of the administrative system. The article defines the essence of the concepts «networking of the educational institutions», «innovative educational network», «University network», «academic University network». It is revealed that in modern pedagogical science there are different typologies of innovative educational networks, which are recognized by the international scientific community, characterizing the studied phenomenon on monocriterial, becriterial and polycriterial basis. The author's classification of campus networks, in which the following types of networks, existing in the system of higher education of the European countries are defined: internal (network of University managers; networks of academic staff; student network (scientific, interest, leadership); subject, networks of scientists, teachers, students) and external University networks (academic network; expert networks; research networks) is presented in the article. The substantive principles of activity of the leading academic campus networks - Europaeum, The Coimbra Group, Utrecht Network are demonstrated by the author. The common features of management of the educational networks, namely: plurality leaders; unifying goal; voluntary relations; multiplicity of levels of interaction; openness, spontaneity; nonhierarchy, decentralization, mainly horizontal or functional cooperation between market participants; openness of networks for «enter» and «exit», public availability of resources (primarily information); equality of the participants in the network, regardless of their role, scope, resources; high mobility; a clear organizational structure are revealed in the article.